Laparoscopy-assisted pancreaticoduodenectomy as minimally invasive surgery for periampullary tumors: a comparison of short-term clinical outcomes of laparoscopy-assisted pancreaticoduodenectomy and open pancreaticoduodenectomy - Mendoza III, Arturo S.; Han, Ho-Seong; Yoon, Yoo-Seok; Cho, Jai Young; Choi, YoungRok (Journal of hepato-biliary-pancreatic sciences, 2015)
Background Few reports have described laparoscopy‐assisted pancreaticoduodenectomy (LAPD) as an alternative to the conventional open approach for periampullary tumors. The safety and feasibility of this procedure remain to be determined. In this study, we compared the short‐term clinical outcomes of LAPD with those of open pancreaticoduodenectomy (OPD). Methods A retrospective review of patients who had undergone pancreaticoduodenectomy for periampullary tumors between June and December 2014 was conducted. Patient demographic data and their pathological and short‐term clinical parameters were compared between the LAPD and OPD groups. Results Fifty‐two patients were included in the study: 18 had undergone LAPD and 34 had undergone OPD. The mean operation time was longer for LAPD than for OPD (531.1 vs. 383.2 min, P < 0.001). The estimated blood loss, rate of blood transfusion, surgical resection margin status, and number of lymph nodes retrieved were similar in both groups. Overall morbidity and the incidence of pancreatic fistula did not differ significantly between the two groups. However, the mean length of hospital stay was significantly shorter in the LAPD group (12.6 vs. 18.6 days, P = 0.001). Conclusion LAPD is a technically safe and feasible alternative treatment for periampullary tumors, with short‐term clinical outcomes equivalent to those of OPD, with a shorter hospital stay. Highlight Mendoza and colleagues set out to evaluate the safety and feasibility of laparoscopy‐assisted pancreaticoduodenectomy (LAPD) for periampullary tumors in comparison with conventional open pancreaticoduodenectomy (OPD). LAPD, which combines the advantages of laparoscopic resection with easier intracorporeal reconstruction, had similar short‐term clinical outcomes, but a significantly shorter hospital stay than OPD.